Behavioral consistency in corporate finance: CEO personal and corporate leverage - Cronqvist, Henrik; Makhija, Anil K.; Yonker, Scott E. (Journal of Financial Economics, 2012)
We find that firms behave consistently with how their CEOs behave personally in the context of leverage choices. Analyzing data on CEOs' leverage in their most recent primary home purchases, we find a positive, economically relevant, robust relation between corporate and personal leverage in the cross-section and when examining CEO turnovers. The results are consistent with an endogenous matching of CEOs to firms based on preferences, as well as with CEOs imprinting their personal preferences on the firms they manage, particularly when governance is weaker. Besides enhancing our understanding of the determinants of corporate capital structures, the broader contribution of the paper is to show that CEOs' personal behavior can, in part, explain corporate financial behavior of the firms they manage.